2020
DOI: 10.1371/journal.pone.0226722
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine neurons do not constitute an obligatory stage in the final common path for the evaluation and pursuit of brain stimulation reward

Abstract: The neurobiological study of reward was launched by the discovery of intracranial selfstimulation (ICSS). Subsequent investigation of this phenomenon provided the initial link between reward-seeking behavior and dopaminergic neurotransmission. We re-evaluated this relationship by psychophysical, pharmacological, optogenetic, and computational means. In rats working for direct, optical activation of midbrain dopamine neurons, we varied the strength and opportunity cost of the stimulation and measured time alloc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(60 citation statements)
references
References 105 publications
7
53
0
Order By: Relevance
“…Some authors propose that a key mechanism of mfb DBS is the antidromic activation of the highly excitable myelinated glutamatergic inputs into the midbrain DA neurons. The dopaminergic projections in turn modulate numerous up‐stream antidepressant effects in the NAC and PFC (Schlaepfer et al., 2014) (Trujillo‐Pisanty et al., 2020). Furthermore, it is not known how optogenetic stimulation of the DA system impacts on the noradrenergic system, although it is recognized that the cross‐talk between the transmitters in stress regulation is important (Isingrini et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors propose that a key mechanism of mfb DBS is the antidromic activation of the highly excitable myelinated glutamatergic inputs into the midbrain DA neurons. The dopaminergic projections in turn modulate numerous up‐stream antidepressant effects in the NAC and PFC (Schlaepfer et al., 2014) (Trujillo‐Pisanty et al., 2020). Furthermore, it is not known how optogenetic stimulation of the DA system impacts on the noradrenergic system, although it is recognized that the cross‐talk between the transmitters in stress regulation is important (Isingrini et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A major challenge for the field-as evidenced by the diversity of research contained within this Collection of papers-is understanding how the findings from individual studies can be integrated to develop a cohesive framework for elucidating how the brain processes rewards and makes decisions. For example, how might the parallel limbs of brain-reward circuitry proposed by Trujillo-Pisanty et al [31] modulate changes in prefrontal activity that occur in response to surprise and uncertainty, as reported by Kluger et al [18] and Shapiro and Grafton [22]? Could risk for developing habitual behaviors be the result of enhanced activity of striatal patches (e.g., striosomes; [33]) that, subsequently, alters the connectivity of the globus pallidus externus in response to psychotropic drugs as was observed by Fede et al [37]?…”
Section: Discussionmentioning
confidence: 99%
“…They found that dopamine manipulations can significantly alter the opportunity cost, but not the strength, of reward-seeking responding reinforced by LH-MFB stimulation. In the present study, Trujillo-Pisanty et al [31] examined the effects of dopamine transporter blockade on reward-seeking responding reinforced by optogenetic stimulation of ventral tegmental dopamine neurons, while varying the reward strength and opportunity cost of the stimulation. The selective dopamine transporter blocker GBR-12909 affected both strength and cost measures of dopamine neuron stimulation.…”
Section: Theme 2: Non-human Animal Investigations Into Reward and Decmentioning
confidence: 99%
“…The counter model implies that beyond the outputs of the activated midbrain dopamine neurons, there is a neural signal, (dubbed "reward intensity") whose amplitude in response to a pulse train of a given duration is a monotonic function of the aggregate firing rate 23 . According to the single-operant matching law 6,[24][25][26] , time allocation is a monotonic function of reward intensity and hence of the aggregate firing rate as well. Thus, during a pulse-duration sweep, time allocation is a monotonic function of pulse duration.…”
Section: From Excitation Of Dopamine Neurons To Behavior and Backmentioning
confidence: 99%